JUAL BELI CASH ON DELIVERY DALAM PERSPEKTIF HUKUM BISNIS ISLAM (STUDI KASUS PADA OLSHOPOOTD_UWIK KEC. PERCUT SEI TUAN KAB. DELI SERDANG) TAHUN 2022 - Ayu Putri Lestari; Eli Agustami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
In the discussion of this thesis, we generally know that buying and selling is carried out directly, namely by a buyer seeing the goods purchased and directly paying for the goods purchased. However, along with the development of buying and selling technology, switching to online where the goods sold by a seller are posted to social media, then the buyer places an order online, and for the goods ordered in this case the payment is made when the goods have arrived. Based on the background of the problem, there are several problem formulations including, What is the form of Buying and Selling Cash On Delivery at Olshoptd_Uwik, and How is the form of buying and selling Cash On Delivery in the perspective of Islamic Business Law. The purpose of this research is no analyze the form of buying and selling cash on delivery at olshooptd_Uwik, and to find out the law of buying and selling cash on delivery in an Islamic business perspective. This research includes qualitative, namely research conducted by analyzing the problem using the method of Observation, Interview and Documentation. Based on the results of the research that has been carried out, it can be concluded that, the Practice of Selling and Buying Cash On Delivery in the Perspective of Islamic Business Law, the case study on Olshoopd_Uwik is a discussion in which buying and selling online is carried out using the Observation/Interview method and reviewed in Islamic Business Law. This review is carried out to find out how to buy and sell cash on delivery online in the perspective of Islamic business law. Because when the author made observations/interviews with Olshoop, he did not know Islamic Business Law in terms of buying and selling cash on delivery, and only knew about the procession he was doing.